THE CONTEXTUAL MEDICAL POLITENESS PRINCIPLE: A MINANGKABAU-BASED PRAGMATIC MODEL OF CULTURAL IDENTITY AND LINGUISTIC SENSITIVITY - Widya Fhitri; Made Sri Satyawati; I Wayan Pastika; I Ketut Artawa (Universitas PGRI Sumatera Barat, 2025)
The Minangkabau people are known as a community whose social behavior is still governed by traditional values. These values have a significant impact on how people communicate with one another. Some of the most commonly used values are the use of proper language based on “kato nan ampek,” or four words. The value of “kato nan ampek” means that the Minangkabau people have a four-level system of communication. These traditional values are inseparable from the culture of the Minangkabau people. This way of communicating is applied to all aspects of life, including the medical environment. In this medical environment, language is used in the context of power and intensity of encounters, so that the communication that takes place will influence meaning, respect, and other values that may arise. This study analyzes linguistic politeness strategies in the medical environment and relates them to Minangkabau cultural identity. Data analysis is explained in terms of Leech's (1983) Politeness Principle and integrated with the branch of intercultural pragmatics, which views politeness as a culturally specific practice rather than a general linguistic phenomenon. This study employs a qualitative research design combining naturalistic observation and thematic discourse analysis to examine interactions between health workers and patients in hospitals in Padang city. The results of the study show that communication among the Minangkabau people in the medical environment is characterized by a strong tendency toward indirect requests, softened commands, and inclusive pronouns, as well as the use of polite forms of address such as “Bapak and Ibu” (Sir and Ma'am). This tendency shows respect and social balance, which can reduce tension between health workers and patients who are consciously not in the same position. The principle of politeness in interactions between health workers and patients in the Minangkabau environment is not only a communicative approach but also one that emphasizes harmonious relationships, relational balance, and ethical considerations. Based on the approach outlined in this communication, the study proposes a new strategy for analyzing the so-called Contextual Medical Politeness Principle (CMPP). CMPP is a development of a previous theory that proves that politeness in medical interactions cannot be separated from the influence of culture and community identity. This principle of politeness is not only a strategy to reduce the risk of losing face, but can also be used as a moral and relational activity rooted in cultural knowledge. This study contributes to the science of linguistic politeness in relation to ethnolinguistics and the moral philosophy of the Minangkabau people. This study shows that the Minangkabau people's communication style is rooted in a regional context that conflicts with the dominant Western paradigm. This study presents a unique pragmatic model of Minangkabau politeness, demonstrating that it is not merely a regional or cultural phenomenon but a broader pragmatic model with implications for comparative research in linguistic politeness, health communication, and sociocultural linguistics in multilingual societies.